Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Pekerjaan Umum Tata Ruang Dan Pertanahan Solok Selatan - Hasanah, Hesky Zaira; Yusri Ilyas; Ibrahim, Akhmad; Eka Sutisna (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2023)
This research aims to find out how much influence Leadership Style and Employee Discipline have on Employee Performance at the South Solok DPUTRP Office. Research variables are Leadership Style (X1), Work Discipline (X2), Employee Performance (Y). The data collection method is through surveys and distributing questionnaires to a sample of 40 people. The research method used in this research is a quantitative method. The influence of leadership style and work discipline on employee performance simultaneously has a positive and significant influence between the variables of leadership style and work discipline on employee performance. Where Fcount> Ftable namely 45,202 > 3.252 and significant at 0.000 < 0.05 then HOrejected and Ha accepted. It is known that the R value is 0.842. This shows that there is a strong relationship between leadership style and work discipline on employee performance. Meanwhile, the R valueSquare of 0.710 or (71%). This shows that there is a positive and significant influence of leadership style and work discipline together on employee performance in the South Solok land and spatial planning public works department.